Anmeldelse af A Brief Introduction to Modern Arabic Literature af David Tresilian - Eksell, Kerstin (Passage - Tidsskrift for litteratur og kritik, 2009)
Review of: A Brief Introduction to Modern Arabic Literature by David Tresilian Written by Kerstin Eksell